Dampak Ekonomi Hijau terhadap Pertumbuhan Ekonomi dan Lingkungan di Indonesia - Sitepu, Dendi Eka Muda; Hasibuan, Bernard (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Green economy is an economic concept that aims to improve community welfare and promote social justice, while minimizing negative impacts on the environment. This concept focuses on the efficient and sustainable use of natural resources, as well as reducing carbon emissions and pollution. A green economy is an economic system that is oriented towards reducing carbon emissions, efficiency in resource use, and social inclusiveness. In Indonesia, the green economy has a very important role in encouraging economic growth. By emphasizing sustainability, resource efficiency and technological innovation, Indonesia can achieve stable and inclusive economic growth, while facing global environmental challenges. This concept also contributes greatly to encouraging innovation, creating jobs, increasing sustainability and attracting investment.